DAMAGE IDENTIFICATION STUDY OF PLATE STRUCTURES BASED ON WAVELET METHOD - LI XuJuan; MIAO BingRong; SHI YanMin; WANG MingYue (Jixie qiangdu)
The location and size assessment of different boundary conditions of plate and the effect of the sensor arrangement and noise for damage identification were carried. The principal process includes: firstly,the natural feature parameters of intact and damaged structures were obtained by the finite element modal analysis of thin plate. Modal nodes displacement data of the rectangle thin plate was decomposed and evaluated using the discrete wavelet transform,and the high frequency information and singular value of the damage location were received. Secondly,damage identification of plate structure under different boundary conditions were performed,and the quantity estimation of damage degree is estimated quantitatively by the change rate of the maximize value of wavelet coefficients. Finally,wavelet coefficient of 4 clamped constraints is bigger than that of 4 simply supported constraints about 0. 5%,and 0. 88% comparing to the 2 clamped constrains. The cases of the size of grid g = 40 m and wavelet de-noising for signal are able to identify plate’s damage,effectively. The study results show that this method is valid for the damage identification of location and damage severity of 2 D plate,which can be expected to provide some thinking and reference value for vehicle structures’ damage identification.